A survey of herbal weeds for treating skin disorders from Southern Thailand: Songkhla and Krabi Province. (4th December 2016) - Neamsuvan, Oratai; Bunmee, Pattaraporn
Abstract: Ethnopharmacological relevance: Skin diseases are common health problems which affecting to all ages. In Thailand, the number of patients diagnosed with skin diseases is increasing every year. Nowadays, The Ministry of Public Health is supporting and promoting herbs for treating various disorders, including disorders of the skin to reduce the problem of antibiotic resistance and adverse drug reactions. This study aimed to: (1) enumerate the herbal weeds for treating skin disorders; (2) study local knowledge of weed utilization for treating skin disorders according to the folk healers in Songkhla and Krabi province; and (3) study quantitative data by Informant consensus factor (ICF), Use value (UV) and Fidelity level (FL) value. Materials and methods: Field surveys and Semi-structured interviews about the local names, parts of plants used, preparation and use method, as well as local properties were done. The data were further analyzed by descriptive statistics, interpretation and quantitative indexes (ICF, UV as well as FL). Results: The results discovered 44 herbal species of weeds belonging to 41 genera in 25 families. The most used plant families were Amaranthaceae (6 species). Most plants were used to treat abscess (18 species; 40.91%). The highest UV was recorded for Commelina benghalensis (0.65). The highest ICF values were found in vitiligo, ringworm, tinea versicolor and burns (1.00 each). The highest FL values were recorded for Cleome gynandra, Cleome viscosa, Sphenoclea zeylanica, Acmella oleracea, Leersia hexandra, Cyperus involucratus, Phyllanthus urinaria and Iresine herbstii (100.00 each). A review of the literatures revealed that 34 plant species had already been tested for their pharmacological activities. The biological activities associated with treatment of skin diseases can be divided into four categories: antimicrobial, anti-inflammatory, wound healing and antioxidant activity. Conclusion: The information indicates that herbal weedy utilization is still importance to the treatment of traditional healers through accumulated experience for a long time. Therefore, this study is a guide to the conservation of folk medicinal knowledge. It might be implied as the basis for drug development and application of herbal weeds to treat skin disorders along with promoting sustainable use of natural resource. Graphical abstract: